Frozen Semen Characteristics of Limousin Bull at Different Ages - A. Baharun; A. B. Setiawan; A. Rahmi; H. Iskandar; M. Gunawan; S. Anwar; T. Maulana; E. M. Kaiin; S. Said (Faculty of Animal Science, Bogor Agricultural University, 2023)
Strategies to increase the population and productivity of beef cattle can be implemented through reproductive management, such as artificial insemination (AI) using frozen semen. This study aims to evaluate the characteristics of frozen semen of Limousin bulls of different ages, which can still be used for insemination programs up to 12 years of age. This study used frozen semen of Limousin bulls ages 3, 8, and 12 years produced in 2021 at the Artificial Insemination Center in Singosari, East Java Province, Indonesia. Five bulls from each different age group were used for replication. Computer-assisted sperm analysis was used to determine sperm motility, viability, and abnormalities using eosin–nigrosine staining. Plasma membrane integrity was analyzed using the hypoosmotic swelling test. The acrosomes’ integrity was evaluated using FITC-PNA-PI, protamine deficiency using chromomycin A3, and DNA fragmentation testing using the acridine orange fluorescent technique. The results showed that the parameters of sperm motility, viability, abnormality, plasma membrane integrity, and protamine deficiency showed no significant differences in all age groups. The kinematic parameters (straightness and beat cross frequency) of the 3-year-old group were significantly higher (p<0.05) compared with those of the other groups. Parameters of acrosome integrity showed a higher prevalence in the 3-year-old group compared with those of the other groups. Furthermore, the DNA fragmentation of the 12-year-old group was significantly higher (p<0.05) compared with that of the other groups. The research concludes that increasing the age of Limousin bulls can reduce acrosome integrity and DNA fragmentation.